State of Food and Agriculture (SOFA) 2024: Background report - Getaneh, Yonas; Nigusse, Yirgalem; Abera, Wuletawu; Mulatu, Kalkidan; Balcha, Yodit; Degefie, Tibebe; Eshete, Meron; Bekele, Mekonen; Tamene, Lulseged D. (2024)
This research serves as a background paper for the FAO-SOFA 2024 report, examining the evolution of hidden costs in Ethiopia's agri-food system. By leveraging insights from the 2023 FAO-SOFA flagship report, the study employs a combination of literature review, stakeholder consultations, and FABLE-based modeling. The total hidden costs of Ethiopia's agri-food system were estimated at 51 billion 2020 PPP dollars per year. The largest contributor to these hidden costs was the social sector, particularly poverty among agri-food workers, which accounts for 24.3 billion 2020 PPP dollars annually. Environmental externalities, including those linked to climate change and land-use change, were the second-largest contributors, totaling 19 billion 2020 PPP dollars per year.